2011
DOI: 10.3102/0002831211410683
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Social Cognitions Predict Sex Differences in Math Engagement and Achievement

Abstract: Gender stereotypes about math and science do not need to be endorsed, or even available to conscious introspection, to contribute to the sex gap in engagement and achievement in science, technology, engineering, and mathematics (STEM). The authors examined implicit math attitudes and stereotypes among a heterogeneous sample of 5,139 participants. Women showed stronger implicit negativity toward math than men did and equally strong implicit gender stereotypes. For women, stronger implicit math=male stereotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
2
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(199 citation statements)
references
References 78 publications
8
172
2
17
Order By: Relevance
“…The negative impact of these associations for STEM women can be seen in work done by Nosek and Smyth [15]: college women, even those majoring in STEM courses, show a strong association between math and maleness and the strength of this association predicts their performance on the quantitative section of the SAT [11]. Interestingly, college men enrolled in STEM courses show the strongest endorsement of the "men are better at math stereotype."…”
Section: Stereotypes About Women's Ability In Stemmentioning
confidence: 95%
See 1 more Smart Citation
“…The negative impact of these associations for STEM women can be seen in work done by Nosek and Smyth [15]: college women, even those majoring in STEM courses, show a strong association between math and maleness and the strength of this association predicts their performance on the quantitative section of the SAT [11]. Interestingly, college men enrolled in STEM courses show the strongest endorsement of the "men are better at math stereotype."…”
Section: Stereotypes About Women's Ability In Stemmentioning
confidence: 95%
“…Although there have been many studies on math and science attitudes of undergraduate women not majoring in STEM, we chose not to include these studies because there is evidence that many women in STEM differ in critical ways from women not in STEM. For example, many STEM women hold different beliefs about STEM related abilities and gender than non-STEM women [15]; and there is some evidence that STEM women tend to be less gender normative in terms of gender roles [16][17][18]. For example, a study of computer science majors found that female majors did not differ from male majors on a sex roles scale, but did significantly differ from female nonmajors [16].…”
Section: Gender Inequalities In College Stem Beyond Retentionmentioning
confidence: 99%
“…Some evidence suggests, however, that people perceive scientists to be more like men than women. Research using the Implicit Association Test (Greenwald, McGhee, & Schwartz, 1998) indicates that people implicitly associate math (Nosek, Banaji, & Greenwald, 2002;Nosek et al, 2007;Nosek & Smyth, 2011) and science (Kessels, Rau, & Hannover, 2006;Lane, Goh, & Driver-Linn, 2012;Nosek et al, 2007) with men more than with women. Moreover, research has found that liking math (Nosek et al, 2002) and the intention to pursue a STEM major or career was associated with implicit stereotypes associating men with scientists (Lane et al, 2012).…”
Section: The Association Of Men With Sciencementioning
confidence: 99%
“…Numerosas investigaciones dejan en evidencia, además, que la actitud negativa hacia el aprendizaje de la matemática es más acusada entre las chicas, y presentan mayores niveles de ansiedad frente a las tareas en éste ámbito, y menores niveles de autoeficacia (Akin, &Kurbanoglu, 2011;Selkirk, Bouchey, &Eccles, 2011). Es posible afirmar que podría haber patrones emocionales en las mujeres basados en factores culturales como creencias y estereotipos de menor dominio en matemáticas y, por ende, más baja competencia en el área (Nosek, &Smyth, 2011). En cuanto a los niños, los resultados no son concluyentes (Belfi, Goos, De Fraine, & Van Damme, 2012).…”
Section: Discussionunclassified